Physical Activity Levels of Greek High School Students - Bertaki Χριστίνα; Michalopoulou Μαρία; Argyropoulou Ευγενία, Χριστίνα; Bitzidou Χρυσούλα (Inquiries in Physical Education and Sport, 2007)
The aim of the present study was to assess physical activity for high school students in Greece and determine gender and high school grade effects on total score of physical activity as well as physical activity of high intensity, of moderate intensity and related to walking. The participants were 517 high school students aged 15-18 (M= 16.74 + 0.8 years), 252 male (16.7+1.8 years) and 265 female students (17.1 + 1.2 years). Physical activity was assessed using IPAQ (Graig et al., 2003), questionnaire which assesses participation in physical activity during the last week. According to the results of the ANOVA (2 x 3) “Gender x High School Grade” on the total score of physical activity, boys were more active than girls (p<.01) and the students of the 3rd grade were the least active group (p<.001). Results of the MANOVA (2 x 3), regarding the intensity of physical activity, revealed a higher participation of boys in physical activities of high intensity (p<.01), while the 3rd graders was the least active group (p<.001) in all 3 variables included in the analysis. In conclusion, a large percentage (79%) of the students were assigned to the health enhancing physical activity group, with boys being more active than girls and participating more in physical activities of high intensity. Students of the 3rd high school grade were the least active group and in particular the female students of the 3rd grade were the only moderately active group in this study.